PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE UNTUK MENINGKATKAN HASIL BELAJAR DI SMPN 3 PANCA RIJANG - Ayu, Fitrah Mutiara; Mustamin; Raehana, Syarifa; Bunyamin, Andi; Sudarmono, Muh Aidil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve student learning outcomes in Islamic Religious Education through the implementation of the Think Talk Write cooperative learning model in class VIII.1 of SMP Negeri 3 Panca Rijang, Sidrap Regency. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles, where each cycle consists of planning, action implementation, observation, and reflection stages. The subjects of this study were 33 students. Data collection techniques used include learning outcome tests, observation, interviews, and documentation. The research instruments used were test sheets to measure student learning outcomes and observation sheets to determine student activities during the learning process. The data analysis technique used was quantitative descriptive analysis for test result data and qualitative descriptive analysis for observation data. The results of the study showed that the implementation of the Think Talk Write learning model was able to improve student learning outcomes in Islamic Religious Education at SMP Negeri 3 Panca Rijang, Sidrap Regency. In the pre-cycle stage, the average score of students was 69.69 with a completion rate of 39% or 13 students who achieved completion. In cycle I, the average score increased to 80.15 with a completion rate of 66.67% or 22 students. Furthermore, in cycle II, the average score increased to 88.63 with a completion rate of 93.94% or 31 students who achieved completion. Furthermore, student learning activities also increased and the learning process became more active, interactive, and enjoyable. Thus, the implementation of the Think Talk Write cooperative learning model is effective in improving student learning outcomes.